Aids atitudes among truck drivers - nascimento, Evania; Moriya, Tokico Murakawa (Brazilian Journal of Sexually Transmitted Diseases, 1999)
Background: Truck drives, dueto their working characteristics long periods away from home and their reference griups tend to adopt attitudes and behaviors that put them in a position where they risk exposure to the HIV/ Aids. They deserve attention and research from health professionals. Objective: Check truck driver’s attitudes concerning Aids, but also try to find out the best points of contact and communication means to involve them in informative and educative campaigns. Methods: A structu-red survey was carried out, consisting of identification items and information about truck driver’s sexual lives during their trips. This survey included a scale of attitudes towards Aids (EA-Aids) developed by Moriya (1992), which showed origine and knowledge of the disease and Aids carrier’s evaluation. The survey used a random sample of 200 truckmen who drove on MG-050 freeway. Results: The survey made it possible to identify that truck drives usually search for different (sexual) partners and constantly use condoms. The EA-Aids showed unfavorable attitudes with r E 0.05 for items such as knowledge of the disease and carrier’s analysis. ln their opinion, the best points of contact with them are gas stations and the best communication means is the radio. Conclusion: The truck drivers show vulnerable behaviors for the risk of HN / Aids contamination and must be target for educative and informative campaigns.